World heritage concepts, management and conservation - Woodward, Simon C.; Cooke, Louise (Archaeologist) (Routledge, Taylor & Francis Group, 2023)
"World Heritage Sites: Concepts, Management and Conservation presents an insight into discussions and debates surrounding the UNESCO World Heritage List, and the properties on it. This book will be of pivotal interest to students and scholars in the fields of tourism, heritage, archaeology, natural resource management and development studies"--